Expanding the Biological Properties of Alkannins and Shikonins: Their Impact on Adipogenesis and Life Expectancy in Nematodes - Arampatzis, Athanasios S.; Tsave, Olga; Kirchweger, Benjamin; Zwirchmayr, Julia; Papageorgiou, Vassilios P.; Rollinger, Judith M.; Assimopoulou, Andreana N. (Frontiers in Pharmacology, 2022)
Alkannin, shikonin (A/S) and their derivatives are naturally occurring hydroxynaphthoquinones biosynthesized in some species of the Boraginaceae family. These natural compounds have been extensively investigated for their biological properties over the last 40 years, demonstrating a plethora of activities, such as wound healing, regenerative, anti-inflammatory, antitumor, antimicrobial and antioxidant. This study aims to extend the current knowledge by investigating the effects of various A/S compounds on two model systems, namely on 3T3-L1 pre-adipocytes and the nematode Caenorhabditis elegans. The former constitutes an established in vitro model for investigating anti-obesity and insulin-mimetic properties, while the latter has been widely used as a model organism for studying fat accumulation, lifespan and the anthelmintic potential. A set of chemically well-defined A/S derivatives were screened for their effect on pre-adipocytes to assess cell toxicity, cell morphology, and cell differentiation. The differentiation of pre-adipocytes into mature adipocytes was examined upon treatment with A/S compounds in the presence/absence of insulin, aiming to establish a structure-activity relationship. The majority of A/S compounds induced cell proliferation at sub-micromolar concentrations. The ester derivatives exhibited higher IC50 values, and thus, proved to be less toxic to 3T3-L1 cells. The parent molecules, A and S tested at 1 μM resulted in a truncated differentiation with a reduced number of forming lipids, whereas compounds lacking the side chain hydroxyl group projected higher populations of mature adipocytes. In C. elegans mutant strain SS104, A/S enriched extracts were not able to inhibit the fat accumulation but resulted in a drastic shortage of survival. Thus, the set of A/S compounds were tested at 15 and 60 μg/mL in the wild-type strain N2 for their nematocidal activity, which is of relevance for the discovery of anthelmintic drugs. The most pronounced nematocidal activity was observed for naphthazarin (NAPH) and β,β-dimethyl-acryl-shikonin(DMAS), followed by isovaleryl-shikonin (IVS). The latter two A/S esters were identified as the most abundant constituents in the mixture of A/S derivatives isolated from Alkanna tinctoria. Taken together, the findings show that the structural variations in the moiety of A/S compounds significantly impact the modulation of their biological activities in both model systems investigated in this study.